1996
DOI: 10.1117/12.241859
|View full text |Cite
|
Sign up to set email alerts
|

Negative resists for electron-beam lithography utilizing acid-catalyzed intramolecular dehydration of phenylcarbinol

Abstract: Acid-catalyzed intramolecular dehydration of phenylcarbinol is used to design highly sensitive negative resists for electron beam lithography. Of the phenylcarbinol resists evaluated in this study, the resist composed of 1,3-bis(a-hydroxyisopropyl)benzene (Diol-1), m/p-cresol novolak resin, and diphenyliodonium triflate (DIT) shows the best lithographic performance in terms of sensitivity and resolution. Fine O.25-j.tm line-and-space patterns were formed by using the resist containing Diol-1 with a dose of 3.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…We developed negative deep-UV resists based on the polarity change reactions such as pinacol rearrangement, [6,7] phenylcarbinol etherification, [8] and phenylcarbinol dehydration, which have low activation energy compared to acidhardening reactions. [9][10][11] In the course of the development of the deep-UV resists, we found that the resist using phenylcarbinols dehydration exhibited high sensitivity, and small pattern-width dependence on PEB temperature. [ 10] Therefore, we expected that the resist using phenylcarbinols would exhibit a good lithographic performance in terms of sensitivity and CD control.…”
Section: Introductionmentioning
confidence: 99%
“…We developed negative deep-UV resists based on the polarity change reactions such as pinacol rearrangement, [6,7] phenylcarbinol etherification, [8] and phenylcarbinol dehydration, which have low activation energy compared to acidhardening reactions. [9][10][11] In the course of the development of the deep-UV resists, we found that the resist using phenylcarbinols dehydration exhibited high sensitivity, and small pattern-width dependence on PEB temperature. [ 10] Therefore, we expected that the resist using phenylcarbinols would exhibit a good lithographic performance in terms of sensitivity and CD control.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5,6] In this article we describe a newly developed resist that uses the ring-chain tautomerism of oacetylbenzoic acid. The formulation, lithographic performance, and insolubilization mechanism of the new resist are discussed.…”
Section: Introductionmentioning
confidence: 99%